When Distrust Goes Viral: Causal Effects of Covid-19 on European Political Attitudes - Gianmarco Daniele; Andrea F.M. Martinangeli; Francesco Passarelli; Willem Sas; Lisa Windsteiger (Center for Economic Studies and Ifo Institute (CESifo), 2020)
To investigate how Covid-19 is shaping the way Europeans think about institutions, we conducted a large online survey experiment during the first wave of the epidemic (June). With a randomised survey ow we varied whether respondents are given Covid-related treatment questions first, before answering the outcome questions. We find that the crisis has severely undermined trust in politicians, the media, the EU and social welfare spending financed by taxes. This is mainly due to economic insecurity, but also because of health concerns. We also uncover a rallying effect around (scientific) expertise combined with populist policies losing ground.
Keywords: D72; H51; H53; H55; O52; P52; 330; Covid-19; institutional trust; political attitudes; online survey experiment; European Union; welfare; taxation; populism